THE CORRELATION BETWEEN THE ONSET OF STROKE AND COGNITIVE IMPAIRMENT - , LEE KAI XIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Stroke or a âbrain attackâ happens when a thrombus blocks an artery, or a blood vessel ruptures, which interrupts the blood flow to the brain. When either of these events occur, brain cells will die due to lack of oxygen supply to the brain and brain damage occurs. This research aims to investigate the correlation between onset of stroke and cognitive impairment using MMSE. Objective : The objective of the study is to find out the correlation between onset of stroke and cognitive impairment Methodology : The method used in this study is cross sectional by using ANOVA test. The population that use here is patients who are admitted into the Stroke Unit in the Neurology Department of RSUP Dr. Sardjito. Result : Statistic test using ANOVA test shows that there is no statistically significant correlation between the onset of stroke and cognitive impairment. Summary : The correlation between onset of stroke and cognitive impairment is not statistically significant.